Influence of simultaneous infestations of Prostephanus truncatus and Sitophilus zeamaison the reproductive performance and maize damage - Rugumamu, C P (Tanzania Journal of Science, 2021)
This study examined the combined effect of Prostephanus truncatus and Sitophilus zeamais infestations on their reproductive performance and on the damage they cause to maize variety ZM 621 with 12.5% moisture content. The specific objective was to determine the number of the insect pests at F1 and F2 and the grain weight losses caused by the simultaneous pests' infestations of shelled maize in the search for a control strategy. The results showed a change in adult insect numbers from F1 to F2. During single infestation the change in P. truncatus was 47.54% while in simultaneous infestations it was 41.66%. The change in S. zeamais was 31.25% and 18.60% during single and simultaneous infestations respectively. The t-test indicated significant differences in the percentage change of adult insect numbers between single and simultaneous infestations at P< 0.01. Further, the grain weight loss in simultaneous infestations was 28.53% while in single infestation P. truncatus and Sitophilus zeamais caused loss of 26.40% and 6.21% respectively. The Kruskal-Wallis test showed a significant difference in weight losses among the infestation types at P < 0.01. The P. truncatus and S. zeamais numbers were positively correlated with the grain weight losses at P < 0.05. It was concluded that simultaneous infestations greatly reduced the reproductive performance of Sitophilus zeamais up to F2 while that of P. truncatus was less affected. These findings thus contribute to the components of Integrated Pest Management (IPM).